INFLUENCE OF INTELLECTUAL CAPITAL AND INSTITUTIONAL OWNERSHIP AT FINANCIAL DISTRESS WITH CASH FLOW OPERATING AS INTERVENING VARIABLE - Eri Kusnanto (Journal of Information Systems and Management (JISMA), 2023)
With operating cash flow as an intervening variable, this study investigates the relationship between institutional ownership, particularly in the context of between 2015 and 2019 there were consumer items listed on the Indonesian stock exchange, affect financial distress. Financial distress is impacted by both cash flow operations and institutional ownership, as well as intellectual capital. The study's shortcomings include that it only tests the hypothesis for a single time period and does not take other factors outside of finance into account. By paying attention to intellectual capital and institutional ownership, the business must be able to keep its operating cash flow steady.